Quality of groundwater in the areas of Oil evidences - صادق عدي; أريج عدره; عبد الكريم العبدلله (Latakia University Journal -Basic Sciences Series, 2022)
The research aims to study the quality of the groundwater in northeast lattakia which the Oil indices spread in several villages (Beit Ismandar, Al-Mulk, Khirbet Solas, Solas). To achieve this aim 13 groundwater samples were collected in winter season (December 2018) and some physical and chemical parameters (temperature T, pH, total Dissolved salt TDS, chloride, nitrate, sulfate, bicarbonate, phosphate, sodium, potassium, magnesium, calcium) were measured, in addition to measure the total hydrocarbons content using gas chromatography mass spectrometry (GC-MS).The results showed that the temperature, TDS and pH were within the permissible limits according to the Syrian standard specification for drinking water. On the other hand, the values ​​of some ions exceeded the permissible limit, such as calcium, magnesium and sulfate which concentration reached 1235.21ppm, and this is characteristic of the water aquifer close to the oil reservoirs. GC-MS analyzes showed the presence of compounds indicative of oil leakage into the groundwater aquifer, where the groundwater contains organic compounds (hydrocarbons, carboxylic acids, aldehydes, phenols, esters and alcohols) resulting from the impact of oil indices on groundwater in the study area. The Piper diagram shows that the groundwater facies were mostly Ca-Cl facies, and the Water Quality Index (WQI) indicated that most of the groundwater samples in the study area were poor to very poor and unsuitable for drinking purposes. Diagram Wilcos shows that grounwater is generally suitable for irrigation but it must treat from the organic compounds before used it.